Pengembangan Modul Materi Lingkaran Berbasis Discovery untuk Siswa SMP - Amrina Rizta; Rusdy A. Siroj; Rani Novaliana (Jurnal Elemen, 2016)
This study aims to produce a module material circle based discovery learning method for junior high school students are valid and practical, as well as having a potential effect. The method used is research and development. Validity module known from the assessment expert on sheet validation stating that the modules developed had been valid, based on the content (content of the material is in conformity with the basic competencies and indicators of learning are formulated), constructs (module subject matter circle in accordance with the teaching methods of discovery), and language (already using the formula sentences communicative, simple, easy to understand, and in accordance with the EYD). Practicality seen from the test results small group. Results of field trial test was obtained 77.5% of the students scored above 75 with an average value of 78.35. Based on these results, the results of student learning using a module that has been developed is quite good.